Acceptance and Commitment Coaching for Music Performance Anxiety: Piloting a 6-Week Group Course With Undergraduate Dance and Musical Theatre Students - Mahony, Sarah E.; Juncos, David G.; Winter, Debbie (Frontiers in Psychology, 2022)
Treatments for students with problematic levels of music performance anxiety (MPA) commonly rely on approaches in which students are referred to psychotherapists or other clinical professionals for individual care that falls outside of their music training experience. However, a more transdisciplinary approach in which MPA treatment is effectively integrated into students’ training in music/performing arts colleges by teachers who work in consultation with clinical psychologists may prove more beneficial, given the resistance students often experience towards psychotherapy. Training singing teachers, and perhaps music teachers at large, to use an evidence-based coaching strategy like Acceptance and Commitment Coaching (ACC) to directly manage students’ MPA is one such approach. Building on the work of a previous study in which ACC was administered by a singing teacher to a musical theatre student with problematic MPA, we piloted the effectiveness of a six-session, group ACC course for a sample of performing arts students (N = 6) with MPA related to vocal performances, using a mixed-methods design. The coach here was also a singing teacher without a clinical background, and her training in ACC by a clinical psychologist was of a similar duration (8 hours) as the previous teacher’s (7 hours). Similar to the musical theatre student, the students reported being significantly less fused with their MPA-related cognitions, more accepting of their MPA-related physiological symptoms, and more psychologically flexible while performing in general, and these improvements were maintained after three months. Furthermore, they appeared to lower their shame over having MPA and change how they thought in relation to one another. Of note, these improvements were similar to those shown by seven vocal students with MPA after they received Acceptance and Commitment Therapy from a clinical psychologist, but with larger reductions in shame and better acceptance of MPA, which suggests a non-clinical, group ACC intervention that includes supportive discussions to normalize MPA and challenges attempts to control it may be more helpful than individual psychotherapy. These results are promising and indicate a brief training in ACC (< 10 hours) may be sufficient for singing teachers to provide significant benefit for students with problematic MPA.